2020
DOI: 10.1186/s13018-020-01984-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of risk correlation between recurrence of patellar dislocation and damage to the medial patellofemoral ligament in different sites caused by primary patellar dislocation by MRI: a meta-analysis

Abstract: Purpose Non-surgical treatment of primary patellar dislocation has a high risk of recurrent dislocation; thus, we tried to identify injuries in which sites of the medial patellofemoral ligament (MPFL) were most associated with recurrent dislocation by analyzing relevant original literature in order to provide improved suggestions on early surgical treatment. Methods According to the preset retrieval strategy, the original studies were retrieved until January 2020 using MEDLINE, Embase and Cochrane Library. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The MPFL is the most important static restraint to the lateral displacement of the patella during the first 30° of flexion [ 76 ]. After the first patellar dislocation, the MPFL is always damaged [ 77 , 78 ] and a ligament reconstruction is often required [ 12 , 79 ]. Patients without imaging evidence of pathoanatomical risk factors are suitable for isolated MPFL reconstruction [ 80 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…The MPFL is the most important static restraint to the lateral displacement of the patella during the first 30° of flexion [ 76 ]. After the first patellar dislocation, the MPFL is always damaged [ 77 , 78 ] and a ligament reconstruction is often required [ 12 , 79 ]. Patients without imaging evidence of pathoanatomical risk factors are suitable for isolated MPFL reconstruction [ 80 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study has shown elevated TT-TG distance, trochlear dysplasia, patella alta and so that 92% of 175 patients had MPFL injury after a first time acute patellar dislocation ( 11 ). Injured sites include the femoral attachment and the patellar attachment ( 12 ). Moreover, a biomechanical study showed that MPFL provides approximately 60% of the inward binding resistance against lateral patella displacement ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…When the femur in motion is subject to internally rotated external force relative to the tibia, the inner surface of the patella bumps into the lateral femoral condyle, and the stress to cortical bone is transmitted to the bone trabecula, resulting in congestion, edema, and hemorrhage of trabecular bone. e different degrees of damage to the trabecular bone occurred due to external stress, and the patella was instantly separated from the trochlear groove, leading to patella dislocation [13][14][15]. e individual differences, and noise and artifacts in MRI images, and other interference factors [16,17], resulted in a certain probability of missed diagnosis in the diagnosis of clinical APD patients.…”
Section: Discussionmentioning
confidence: 99%